Steven Johnson Author Talk Poster - Kansas State University, K-State First (Kansas State University. K-State First., 2014)
A poster advertising an author talk by Steven Johnson at Kansas State University on September 3, 2014. Steven Johnson's book "The Ghost Map" was the 2014-2015 common book.
Keywords: First-year experience program; Common reading program; Engagement; Events; Author visit; Ghost Map, The; Promotional materials